Pemberdayaan Kelompok Perempuan dalam Pembuatan Makanan Pendamping ASI di Desa Sukanagalih, Cianjur - Lina Agestika; Angga Rizqiawan; Ernie Halimatushadyah; Ratnayani Ratnayani; Tri Ardianti Khasanah (Jurnal Abdimas Kesehatan (JAK), 2023)
.Malnutrition among underfive children is closely related to adequate intake in the first 1000 days of life; starting with breastfeeding and complementary foods. Failure to meet food intake in children over the age of two can result in irreversible growth retardation. This community service activity was carried out in Sukanagalih Cianjur Village in August 2023. This activity empowered women's groups to increase knowledge about complementary foods and make local-based recipes for complementary foods. Community service activities began with a local food survey in the surrounding environment, implementation of a nutrition education program, and a demonstration of the process of cooking complementary foods for breast milk, followed by a group competition for mothers and recording of all recipes made by the community. From 40 participants, knowledge of 22 mothers who took part in the activity, were assessed through a pre-posttest questionnaire. The pre and post test results were collected and analyzed using the Wilcoxon test by considering the distribution of the data. The results showed that there was an increase in mother's knowledge regarding the processing and nutritional content of good Complementary Food for under-five with a median score of 75 to 80 (p-value: 0.039). Participants also started to feel confident with their recipe creations to improve the nutritional status of children around the village. The food ingredients in the recipe are also easy to obtain so they have the potential to be used for the monthly cycle complementary food menu at Posyandu